1966
DOI: 10.1103/physrev.152.1325
|View full text |Cite
|
Sign up to set email alerts
|

Pion-Nucleon Scattering in theP11State

Abstract: The Pn pion-nucleon scattering amplitude is studied in order to determine the dynamical status of the nucleon. A simple one-channel static model is constructed in which a good fit to the low-energy data is obtained with a Castillejo-Dalitz-Dyson (CDD) pole. If there is, in fact, such a pole, with the strength indicated by our model, then one must conclude that other channels play a significant, although not overwhelming, part in forming the nucleon. It is also possible to reconcile all the available informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1968
1968
1974
1974

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Rev. Letters 17, 1303(1966. 14 The electromagnetic self-mass will diverge in this case because of the slow q 2 variation of the Pomeranchukon contribution.…”
mentioning
confidence: 99%
“…Rev. Letters 17, 1303(1966. 14 The electromagnetic self-mass will diverge in this case because of the slow q 2 variation of the Pomeranchukon contribution.…”
mentioning
confidence: 99%
“…Since 8® 10 does not_contain 10, iV^>io scattering would play no role for a 10 resonance. This argument, of course, begs the question somewhat, but other calculations 19 have already indicated that the role of the TN* channel is not a large one.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, N* and N exchange in a single-channel model do not bind the nucleon if physical couplings are em-ployed. 19 However, such calculations have not included the additional channels arising in Ps-B 8 scattering. By ignoring the inelastic contributions in the calculation given here, we find the same result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking account of the width of 0, we adopt the following definition for P2: I8 It is very difficult to know the details of the left-hand discontinuities, especially when the channel coupling plays an important role. We are interested in the gross features of them and adopt the pole approximation as (10) We put…”
mentioning
confidence: 99%